THE NEWEST METHODS OF VISUALIZING EDUCATIONAL MATERIAL DURING THE TRAINING OF FUTURE TEACHERS (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2023)
The article deals with questions concerning the use of visualization in the educational process,namely the use of the latest innovative method of "scrabble". The research has been carried out to determine thefeatures of this method, the classification is given according to the specified conditions, in particular: on the time ofreproduction (scribing presentation, video scribing), in the form of engagement (drawing, application, magnetic,flannelography, 3D-scribing). A number of skills, which the teacher should have for the successful application of thismethod, is determined. Also in the article there are 6 main stages of development of the program for qualitativereproduction of the main key moments of the report. A number of main advantages defining this method and provingthe necessity of its use for qualitative education of future teachers are determined. Speaking as an auxiliary means ofteaching, he provides significant benefits to the teacher, from the growth of his professional level and the expansion ofhis discipline knowledge, completing the original, non-standard way of presenting the teaching material, taking intoaccount the time saving for the explanation and availability of teaching of significant volumes of complex material;students, from the perception of the new material, its analysis, structuring and memorization, completing interestedlistening, studying and qualitative reproduction of the heard and seen.